Longitudinal changes in body composition and metabolic profile between exercise clinical trials in men with chronic spinal cord injury. (1st November 2016) - Gorgey, Ashraf S.; Martin, Heather; Metz, Alyse; Khalil, Refka E.; Dolbow, David R.; Gater, David R.
Abstract : Study design : Longitudinal design. Objectives : The study was undertaken to determine the effects of cessation of exercise interventions on body composition and metabolic profiles in men with chronic SCI. Settings : Clinical trials within a Medical Center. Methods : Eleven men with motor complete SCI were followed on average over a period of 2.5 years. Six men were involved in two different exercise interventions (functional electrical stimulation cycling versus arm cycling ergometer), 5 days/week for 16 weeks (exercise group), and five men served as a control (control group). Anthropometrics and dual energy X-ray absorptiometry (DXA) were captured to measure changes in lean mass (LM), fat mass (FM), percentage FM before, immediately after exercise, and after a period of 2.5 years. Basal metabolic rate (BMR) and lipid panel were also measured. Results : Thigh circumference increased by 8.5% following exercise (P = 0.042) and remained 6.4% greater than baseline measurements (P = 0.012). Leg LM increased by 9% following the exercise intervention (P = 0.03) and decreased by 16% in the follow-up visit (P = 0.02). Percentage trunk and total body FM increased by 4.5% (P = 0.008) and 3.5% (P = 0.019) in the follow-up visit, respectively, and whole body LM increased by 8.4% and decreased back by 5.4% following a 2.5 year-period. BMR significantly decreased by 15.5% following the exercise (P = 0.029) interventions. Conclusion : Exercise training is accompanied with positive changes in body composition as well as compensatory decrease in BMR, that regressed back following 2.5 years of exercise cessation. Participation in an exercise trial is unlikely to confound the measurements of a follow-up trial.